Advances in Plant Breeding Strategies: Fruits Volume 3 (Springer International Publishing, 2018)
Plant breeders and geneticists are under constant pressure to sustain and expand food production by using innovative breeding strategies and introducing minor crops, which are well adapted to marginal lands, provide a source of nutrition, and have abiotic and biotic stress tolerance, to feed an ever-increasing human population. The basic concept of this book is to examine the use of innovative methods augmenting traditional plant breeding towards the improvement and development of new crop varieties, under the increasingly limiting environmental and cultivation factors, to achieve sustainable agricultural production and enhanced food security. Two volumes of the book series Advances in Plant Breeding Strategies were published in 2015 and 2016, respectively; Volume I: Breeding, Biotechnology and Molecular Tools and Volume II: Agronomic, Abiotic and Biotic Stress Traits. This is Volume 3: Fruits, which is focused on advances in breeding strategies for the improvement of individual fruit crops. It consists of 23 chapters grouped into three parts, according to distribution classification of fruit trees: Part I, Temperate Fruits, Part II, Subtropical Fruits, and Part III, Tropical Fruits. Each chapter comprehensively reviews the contemporary literature on the subject and reflects the authors own experience. Chapters are written by internationally reputable scientists and subjected to a review process to assure quality presentation and scientific accuracy. Each chapter begins with an introduction covering related backgrounds and provides in-depth discussion of the subject supported with high quality color photos, illustrations and relevant data. The chapter concludes with recommendations for future research directions, a comprehensive list of pertinent references to facilitate further reading, and appendixes of genetic resources and concerned research institutes. This book series is a valuable resource for advanced students, researchers, scientists, commercial producers and seed companies as well as consultants and policymakers interested in agriculture, particularly in modern breeding technologies.